2014
DOI: 10.1364/oe.22.017030
|View full text |Cite
|
Sign up to set email alerts
|

RF noise induced laser perturbation for improving the performance of non-resonant cavity enhanced absorption spectroscopy

Abstract: We present a novel strategy for suppressing mode structure which often degrades off-axis cavity enhanced absorption spectra. This strategy relies on promoting small, random fluctuations in the optical frequency by perturbing the injection current of the diode laser source with radio frequency (RF) bandwidth-limited white noise. A fast and compact oxygen sensor, constructed from a 764 nm vertical-cavity surface-emitting laser (VCSEL) and an optical cavity with re-entrant configuration, is employed to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 22 publications
(24 reference statements)
0
17
0
Order By: Relevance
“…A significant example is the recent work by Ciaffoni and co-workers [35] who have developed a sensor for the determination of oxygen consumption (VO 2 ) on a breath-by-breath basis at the mouth of an intubated patient undergoing anesthesia and/or mechanical ventilation. The analyzer, termed a molecular flux sensor (MFS), uses diode laser absorption within an optical cavity [41] in combination with a state-of-the-art flow meter. The latter is instantly adaptable (10 ms resolution) to changing gas compositions.…”
Section: Laser Absorption Spectroscopymentioning
confidence: 99%
“…A significant example is the recent work by Ciaffoni and co-workers [35] who have developed a sensor for the determination of oxygen consumption (VO 2 ) on a breath-by-breath basis at the mouth of an intubated patient undergoing anesthesia and/or mechanical ventilation. The analyzer, termed a molecular flux sensor (MFS), uses diode laser absorption within an optical cavity [41] in combination with a state-of-the-art flow meter. The latter is instantly adaptable (10 ms resolution) to changing gas compositions.…”
Section: Laser Absorption Spectroscopymentioning
confidence: 99%
“…A current noise source is capacitively coupled to the laser diode current supply in an attempt to reduce the mode quality of the laser, so that residual cavity mode noise is reduced. 40,41 The laser temperature is…”
Section: Acetone Detection Strategymentioning
confidence: 99%
“…[18] An alternative method for improving the sensitivity of OA-CEAS was demonstrated by Ciaffoni et al, who showed that the introduction of random frequency fluctuations induced by mixing broadband radio-frequency (RF) noise with the driving current of a VCSEL operating at 764 nm resulted in residual mode noise suppression. [19] Similarly, Manfred et al have shown that the sensitivity of a QCL based OA-CEAS spectrometer was enhanced by nearly an order of magnitude by employing the same current perturbation scheme. [20] The residual mode noise suppression resulting from perturbation of the injection current is due to laser linewidth broadening, making it clear that tuned linewidth sources are advantageous in a laser spectrometer of this type.…”
mentioning
confidence: 90%
“…As broadband RF noise is added to the injection current, the Lamb-dip profile becomes progressively more Gaussian; this is expected since the added noise is white, bandwidth limited and hence not statistically correlated. [19] The impact of introducing RF perturbations to the injection current is also investigated through acquiring the noise PSD of the system, S δν ( f ), where δν represents the laser frequency deviation around its centre value. In order to do this, an opti-cal frequency discriminator is necessary to convert frequency fluctuations into amplitude fluctuations.…”
mentioning
confidence: 99%